THE SIGNIFICANCE OF NONVERBAL COMMUNICATION IN INTERCULTURAL COMMUNICATION: HOW CAN NONVERBAL CUES BE UTILIZED TO PREVENT MISUNDERSTANDINGS AND ENHANCE COMMUNICATION? - Khudoyberdieva Zumrat Khudayberdievna (International Multidisciplinary Journal for Research & Development, 2024)
Nonverbal communication (NVC) plays a pivotal role in intercultural communication, significantly impacting understanding between individuals from diverse cultural backgrounds. This article delves into the significance of NVC in intercultural interactions. It explores how nonverbal cues, such as facial expressions, gestures, posture, proxemics, and eye contact, can be employed to prevent misunderstandings and enhance communication. Additionally, it provides practical tips for the effective utilization of NVC in intercultural encounters.